Penerapan Algoritma Secure Hash Algorithm (SHA) Keamanan Pada Citra - Sembiring, Hermansyah; Manik, Fuzy Yustika; Zaidah, Tengku (MEANS (Media Informasi Analisa dan Sistem), 2019)
Current information exchange is not only in the form of text, it can be an image or video. All of that can be done using computer network technology in the form of the internet. Through an internet connection, you can connect with many people. Cryptography aims for messages or images that cannot be seen by other parties who have no interest in the information. Messages or secured images can be data stored in secure computer memory or sent through computer networks. And can protect the confidentiality of images from various threats that arise. To maintain data security, SHA-256 is used when transforming data bytes into string hashes. The system built has been able to implement the SHA 256 algorithm which can change the original image file in the form of unknown files and encrypted images that are difficult to know the original image, unless read using an application that has been built. the image when encrypted and used again at the time of decryption with as many as 45 characters and may be in the form of numbers or letters. The SHA 256 process when encrypted in only one round, can be played with decryption.